Molecular analysis of five controversial Balkanic species of Allolobophora (sensu lato) Eisen, 1873 (Lumbricidae, Clitellata) with emendation of the genus Cernosvitovia Omodeo, 1956 - Popović, Filip J.; Stojanović, Mirjana M.; Domínguez, Jorge; Sekulić, Jovana M.; Trakić, Tanja B.; Marchán, Daniel F. (Zootaxa, 2022)
Allolobophora (sensu lato) is one of the most controversial genera in the taxonomy of Lumbricidae. Due to its poor definition, this genus is plagued by extensive taxonomic confusion, and its generic composition and internal relationships have remained uncertain, especially in species of the Balkan Peninsula. In this study, we have combined the study of morphological data and molecular phylogenetics based on five genetic markers, regions of the nuclear 28S rRNA and mitochondrial 16S rRNA, 12S rRNA, NADH dehydrogenase (ND1) and cytochrome oxidase C subunit 1 (COI), to delimit the taxonomic status of five controversial Balkanic endemic species, Allolobophora (s.l.) dofleini, Allolobophora (s.l.) serbica, Allolobophora (s.l.) strumicae, Allolobophora (s.l.) paratuleskovi and Allolobophora (s.l.) treskavicensis, sampled in the Kopaonik Mountain. Phylogenetic analyses based on our sampling of these five species recovered a well-supported clade containing the species Allolobophora (s.l.) robusta, Allolobophora (s.l.) mehadiensis mehadiensis, Allolobophora (s.l.) sturanyi dacica, Cernosvitovia rebeli and Cernosvitovia dudichi. Based on these results and previous evidence, the aforementioned Balkanic species are transferred to a redefined Cernosvitovia. We further present a revised list of all species currently included in Cernosvitovia., which includes now 21 species and subspecies taxa, 13 of them newly combined here. Serbiona Mršić & Šapkarev, 1988 is considered a junior synonym of Cernosvitovia Omodeo, 1956.